The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1094/cchem-11-10-0169
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Release of β‐Glucan and Pectin Using an In Vitro Method

Abstract: Cereal Chem. 88(4):385-390The release of soluble dietary fiber is a prerequisite for viscous effects and hence beneficial health properties. A simple in vitro method was adapted to follow the release during gastrointestinal digestion, and the percentage of solubilized fiber was measured over time. β-Glucan from oat bran was mainly released during gastric digestion while the release of pectin from sugar beet fiber continued in the small intestine. Unmilled fractions of sugar beet fiber released more soluble fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…This increase of viscosity during small intestine digestion is possibly a result of the reformed aggregates (Dikeman and others 2006). Ulmius and others (2011) also observed that the pure β‐glucan fractions showed an extensive increase in size during small intestine digestion. The reason could be that the pure β‐glucan was partly depolymerized during gastric digestion and the smaller polymers increased the degree of aggregation due to their higher rate leading to more condensed aggregates and, ultimately, gels in neutralized pH (Li and others 2011).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This increase of viscosity during small intestine digestion is possibly a result of the reformed aggregates (Dikeman and others 2006). Ulmius and others (2011) also observed that the pure β‐glucan fractions showed an extensive increase in size during small intestine digestion. The reason could be that the pure β‐glucan was partly depolymerized during gastric digestion and the smaller polymers increased the degree of aggregation due to their higher rate leading to more condensed aggregates and, ultimately, gels in neutralized pH (Li and others 2011).…”
Section: Introductionmentioning
confidence: 76%
“…Ulmius and others (2011) reported in their study that the release of oat‐β‐glucan was mainly due to gastric digestion. They further observed that the process of milling to smaller particles could improve the releasability of β‐glucan from 20% to 55%.…”
Section: Introductionmentioning
confidence: 99%
“…Iron, zinc, and calcium accessibility was determined by in vitro gastrointestinal digestion using dissolution equipment (model PTWS 800 D, Pharma Test, Hainburg, Germany). In vitro gastrointestinal digestion was performed according to the method described by Ulmius et al . with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Iron, zinc, and calcium accessibility was determined by in vitro gastrointestinal digestion using dissolution equipment (model PTWS 800 D, Pharma Test, Hainburg, Germany). In vitro gastrointestinal digestion was performed according to the method described by Ulmius et al 21 with slight modifications. Five grams of sample was mixed with 200 mL simulated gastric fluid (0.4 g NaCl, 1.4 mL HCl 1 mol L -1 , pH 1.2, in 200 mL deionized water) and 0.64 g pepsin (the pepsin was from gastric mucose, ≥ 250 units mg −1 solid) (Sigma-Aldrich, St. Louis, USA).…”
Section: Fermentation Processmentioning
confidence: 99%
“…Bladder and bowel conditions, intestinal colic and bedwetting have all been helped by soaking in a bath of Oat Straw. These effects of oat β-glucan were well reviewed by Mälkki and Virtanen (2001), Ulmius et al (2011), Wang et al (2002 and Dikeman et al (2006).…”
Section: Other Benefitsmentioning
confidence: 87%